1993
DOI: 10.1007/bf00122278
|View full text |Cite
|
Sign up to set email alerts
|

Bone ingrowth behaviour of hydroxyapatite-coated, polyethylene-intruded and uncoated, sandblasted pure titanium implants in an infected implantation site: an experimental study in miniature pigs

Abstract: We studied the dynamics of bone tissue ingrowth into the pores of hydroxyapatite-coated (plasma-spraying technique) and uncoated wire meshes of pure Ti in an infected implantation site. Samples of the test materials were implanted into the femora of 15 adult G6ttingen minipigs. Just before implantation they were contaminated with Staphylococcus aureus. The pigs were killed after 4, 8, 12 or 24 weeks. Undecalcified ground sections of bone tissue were prepared and stained with toluidine blue for comparative hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
2
Order By: Relevance
“…These data, in combination with the negative correlation between the number of colony forming units at sacrifice with the distal bone contact, indicate when bone‐implant contact is considered to be related to implant fixation,33 that a clear relationship exists between peri‐implant infection and decreased implant fixation. Wilke et al34 demonstrated for HA‐coated implants good osseous ingrowth behavior in spite of local infection. We therefore speculate that the histomorphometrical findings were not directly related to the implant type, but related to the severity of the infection, because the HA implants revealed more severe infections 22.…”
Section: Discussionmentioning
confidence: 99%
“…These data, in combination with the negative correlation between the number of colony forming units at sacrifice with the distal bone contact, indicate when bone‐implant contact is considered to be related to implant fixation,33 that a clear relationship exists between peri‐implant infection and decreased implant fixation. Wilke et al34 demonstrated for HA‐coated implants good osseous ingrowth behavior in spite of local infection. We therefore speculate that the histomorphometrical findings were not directly related to the implant type, but related to the severity of the infection, because the HA implants revealed more severe infections 22.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The same biomaterials were applied in patients. The results using osseointegration of HA, titanium, and PE in animal experiments and in patients were comparable to those (cell adherence and ECM) in the cell culture system).…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with earlier findings (Tonino et al 1999) and confirms that bone ongrowth to the stem followed a normal pattern in this patient, notwithstanding the infection. Experimental studies in miniature pigs also have shown good osseous ingrowth of bone with HA-coated implants despite a local infection (Wilke et al 1993). Rabbit studies have shown that local infection can affect histomorphometric parameters: in severe infections, the bone-implant contact ratio has been found to be smaller in HA implants than in uninfected HA implants and uncoated implants (Oosterbos et al 2002).…”
Section: Discussionmentioning
confidence: 99%